General anesthesia but not conscious sedation improves functional outcome in patients receiving endovascular thrombectomy for acute ischemic stroke: A meta-analysis of randomized clinical trials and trial sequence analysis - Lee, Chia-Wei; Chang, Yang-Pei; Huang, Yen-Ta; Hsing, Chung-Hsi; Pang, Yu-Li; Chuang, Min-Hsiang; Wu, Su-Zhen; Sun, Cheuk-Kwan; Hung, Kuo-Chuan (Frontiers in Neurology, 2022)
Background This study aimed at comparing the difference in prognostic outcomes between patients receiving general anesthesia (GA) and conscious sedation (CS) for endovascular thrombectomy after acute ischemic stroke. Methods Databases from Medline, Embase, Google scholar, and Cochrane library were searched for randomized controlled studies (RCTs) comparing patients undergoing GA and CS for endovascular thrombectomy following anterior circulation ischemic stroke. The primary outcome was frequency of 90-day good functional outcome [defined as modified Rankin Scale score of ≤ 2], while secondary outcomes included successful recanalization rate (SRR) [i.e., modified thrombolysis in cerebral infarction = 2b or 3], mortality risk, symptomatic intracranial hemorrhage (ICH), procedure-related complications, hypotension, pneumonia, neurological outcome at post-procedure 24–48 h, and puncture-to-recanalization time. Results Six RCTs including 883 patients published between 2016 and 2022 were included. Merged results revealed a higher SRR [risk ratio (RR) = 1.11, 95% CI: 1.03–1.2, p = 0.007; I2 = 29%] and favorable neurological outcomes at 3-months (RR = 1.2, 95% CI: 1.01–1.41, p = 0.04; I2 = 8%) in the GA group compared to CS group, without difference in the risk of mortality (RR = 0.88), symptomatic ICH (RR = 0.91), procedure-related complications (RR = 1.05), and pneumonia (RR = 1.9) as well as post-procedure neurological outcome (MD = −0.21) and successful recanalization time (MD = 3.33 min). However, GA was associated with a higher risk of hypotension compared with that of CS. Conclusion Patients with acute anterior circulation ischemic stroke receiving GA were associated with a higher successful recanalization rate as well as a better 3-month neurological outcome compared to the use of CS. Further investigations are warranted to verify our findings. Systematic review registration www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022342483, identifier: CRD42022342483.